Research trends on RME and self-confidence in the Mathematics education curriculum - Rohim Abdurohim; Dinn Wahyudin; Lia Susanti (Inovasi Kurikulum, 2025)
Realistic Mathematics Education (RME) has been recognized as an innovative approach that effectively improves mathematical skills and students' self-confidence. This study aims to analyze scientific trends related to the application of RME and its impact on self-confidence in mathematics education curriculum. A bibliometric approach was used to analyze 200 articles published between 2020-2024. Data were obtained using the Publish or Perish tool and analyzed with VOSviewer to evaluate citation metrics, collaboration patterns between authors, and relationships between keywords. The analysis results showed 2,314 citations with an average of 11.57 citations per article and active collaboration patterns with an average of 2.6 authors per article. This study found that the Realistic Mathematics Education (RME) approach significantly increased students' confidence in learning mathematics and improved problem-solving skills and in-depth concept understanding. The bibliometric analysis showed that research topics related to RME and student confidence have received extensive academic attention, with high citation rates and significant contributions to the development of mathematics education theory and practice. The findings confirm the importance of RME as an innovative approach in supporting students' cognitive and affective learning outcomes while providing a basis for developing mathematics education practice.   Abstrak Realistic Mathematics Education (RME) telah dikenal sebagai pendekatan inovatif yang efektif dalam meningkatkan kemampuan matematis sekaligus kepercayaan diri (self-confidence) peserta didik. Penelitian ini bertujuan untuk menganalisis tren ilmiah terkait penerapan RME dan dampaknya terhadap self-confidence dalam kurikulum pendidikan Matematika. Pendekatan bibliometrik digunakan untuk menganalisis 200 artikel yang diterbitkan pada rentang waktu 2020–2024. Data diperoleh menggunakan perangkat Publish or Perish dan dianalisis dengan VOSviewer untuk mengevaluasi metrik sitasi, pola kolaborasi antarpenulis, dan hubungan antar kata kunci. Hasil analisis menunjukkan total 2.314 sitasi dengan rata-rata 11,57 sitasi per artikel, serta pola kolaborasi aktif dengan rata-rata 2,6 penulis per artikel. Penelitian ini menemukan bahwa pendekatan Realistic Mathematics Education (RME) secara signifikan meningkatkan kepercayaan diri siswa dalam pembelajaran Matematika, selain meningkatkan kemampuan pemecahan masalah dan pemahaman konsep secara mendalam. Analisis bibliometrik menunjukkan bahwa topik penelitian terkait RME dan kepercayaan diri peserta didik telah mendapatkan perhatian akademik yang luas, dengan tingkat sitasi yang tinggi dan kontribusi signifikan terhadap pengembangan teori dan praktik pendidikan Matematika. Temuan ini menegaskan pentingnya RME sebagai pendekatan inovatif dalam mendukung hasil belajar kognitif dan afektif peserta didik, sekaligus memberikan dasar bagi pengembangan praktik pendidikan Matematika. Kata Kunci: analisis bibliometrik; kepercayaan diri; pendidikan matematika; realistic mathematics education; RME